Lectio divina – w poszukiwaniu teologicznych implikacji biblioterapii - Szemplińska, Anna (2017)
The article aims to clarify the method of reading the Holy Scripture, which was born in the medieval cenobic communities. Lectio divina is the ability to read the Bible and its commentary that allows the reader to unite with God. The text of the article explains the historical background of exploring the Bible and points to the Tradition of the Church, which has been associated with the followers of the Sacred Scripture for centuries. Nowadays, the Catholic Church, since the Second Vatican Council, again encourages the faithful to take the effort and study the Scripture in order to progress in spiritual development. It seems that the practice of lectio divina by the believers has a great influence on their physical and mental condition, so it can be argued that the method of reading lectio divina also has a bibliotherapeutic effect.
Keywords: oratio (prayer); contemplatio (listening); Bible; meditatio (meditation); lectio divina